2013
DOI: 10.1038/emboj.2013.100
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysone triggered PGRP-LC expression controls Drosophila innate immunity

Abstract: Throughout the animal kingdom, steroid hormones have been implicated in the defense against microbial infection, but how these systemic signals control immunity is unclear. Here, we show that the steroid hormone ecdysone controls the expression of the pattern recognition receptor PGRP-LC in Drosophila, thereby tightly regulating innate immune recognition and defense against bacterial infection. We identify a group of steroid-regulated transcription factors as well as two GATA transcription factors that act as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
180
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(194 citation statements)
references
References 94 publications
(151 reference statements)
13
180
1
Order By: Relevance
“…Several previous studies suggested that 20E could promote both cellular and humoral innate immunity, and this enhancement requires EcR in Drosophila (13)(14)(15)20). However, knowledge about the effects of 20E on immune response is very limited in lepidopteran insects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies suggested that 20E could promote both cellular and humoral innate immunity, and this enhancement requires EcR in Drosophila (13)(14)(15)20). However, knowledge about the effects of 20E on immune response is very limited in lepidopteran insects.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proven that RNAi-mediated depletion of EcR gene could prevent 20E signal transduction (13,15,31). We then knocked down the expression of the silkworm EcR gene using dsRNA to further investigate the role of ecdysone on the silkworm immunity.…”
Section: Effects Of 20e On Silkworm Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Ecdysone also was reported to regulate the activity of the Imd pathway in adult flies via its target genes, whose products are needed for PGRP-LC expression. In addition, some of these proteins appear to directly regulate the expression of a subset of the Imd pathway target genes (96).…”
Section: Regulation Of the Imd Signaling Pathwaymentioning
confidence: 99%
“…Humoral and cellular immune responses are usually studied in both larvae and adults. Since the maturation of immune responsiveness is strongly dependent on ecdysone [9,10], immune pathways in the adult stage are less affected by developmental timing. It should be noted that AntiMicrobial Peptides (AMPs) (and many immune genes) show very high levels of inducibility (equivalent to heat-shock genes).…”
Section: Introductionmentioning
confidence: 99%